2005
DOI: 10.1080/02844310410035410
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intraoral radiography and computed tomography in evaluation of formation of bone after grafting for repair of residual alveolar defects in patients with cleft lip and palate

Abstract: For one year we studied postoperative computed tomograms (CT) and intraoral radiographs for 29 patients with unilateral alveolar clefts. Interdental bone height and the bony boundary on the nasal side were assessed on intraoral films and compared with the evaluation by CT. Twenty-four cases had adequate interdental bone height as assessed by intraoral films. However, 10 of these 24 cases showed insufficient anteroposterior depth on CT. Two of the remaining five cases were also overestimated by the intraoral ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
14

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 13 publications
0
15
0
14
Order By: Relevance
“…Enemark et al 41 found that although ABG patients seemed to enjoy 90% success rates, as observed on short-term radiographic examination, the later clinical results were poor; cleft closure succeeded in fewer than half the patients. Iino et al 42 compared intraoral radiography and CT in the evaluation of bone formation after SABG in patients with CLP. In all, 24 cases had adequate interdental bone height as assessed by using intraoral radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…Enemark et al 41 found that although ABG patients seemed to enjoy 90% success rates, as observed on short-term radiographic examination, the later clinical results were poor; cleft closure succeeded in fewer than half the patients. Iino et al 42 compared intraoral radiography and CT in the evaluation of bone formation after SABG in patients with CLP. In all, 24 cases had adequate interdental bone height as assessed by using intraoral radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the thickness of the alveolar bone bridge is an important determinant of the success of full oral and dental rehabilitation in patients with cleft lips and palates (Enemark et al, 1987; Lee et al, 1995; Iino et al, 2005). Studies about dental implant prostheses have indicated that a minimum thickness of 1.5 mm is necessary at the surface where dental implants are to be placed so as to provide additional protection and coverage of implants in buccolingual sites (Abyholm et al, 1981; Kim et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al (1995) stated that intraoral dental radiography was an inaccurate gauge of clinical orthodontic decisions because it failed to detail the depth and volume of the bony bridge. Iino et al (2005) indicated that in 41% of cases where, based on intraoral radiographs, the interdental bone height was regarded as a successful surgical outcome the labiolingual thicknesses were actually revealed to be less than the root width of the cleft-adjacent teeth on CT. Inconsistent findings in patients after bone grafting, with success in short-term radiographic examinations and less satisfactory clinical results in later follow-up, were reported by Enemark et al (1987), who found that the successful rate of alveolar bone grafting in intraoral radiographs was 90%, whereas orthodontic cleft closure succeeded in fewer than half the patients.…”
mentioning
confidence: 99%
“…95,96,99,166 Σημαντικές προσπάθειες έχουν γίνει για την αξιολόγηση της τρισδιάστατης μορφολογίας της οστικής γέφυρας. [167][168][169]…”
Section: ακτινογραφικες κλιμακες αξιολογησης της επιτυχιας συγκλεισης γναθοσχιστιαςunclassified
“…Πρώτον, μέσω οπισθοφατνιακών ή ακτινογραφιών δήξεως, δεν υπάρχει δυνατότητα αξιολόγησης του χειλεο-υπερώιου πλάτους της οστικής γέφυρας, που αποτελεί σημαντική παράμετρο τόσο για τις ορθοδοντικές μετακινήσεις, όσο και για την πιθανή τοποθέτηση εμφυτεύματος. 167,168,188 Δεύτερον, η λήψη απλών ακτινογραφιών παρουσιάζει ποικιλία απεικονιστικών προβλημάτων, μεταξύ των οποίων η παραμόρφωση της εικόνας, η αλληλεπίθεση δομών και η δυσκολία στην τοποθέτηση του ασθενούς. 189,190 Η προσπάθεια αριθμητικής διόρθωσης της παραμόρφωσης, που επιχειρείται από την κλίμακα Long, δεν ακυρώνει τα υπόλοιπα προβλήματα.…”
Section: κλίμακες βασιζόμενες σε υπολογιστική τομογραφίαunclassified